Corrosion inhibition by fruit extracts -Inhibition of corrosion of mild steel in simulated concrete pore solution prepared in sea water by an aqueous extract of apple juice- A Case study - Rajendran Susai; Abdulhameed Al-Hashem; Arjunan Krishnaveni; Little Jewelcy Arockiaraj; Gurmeet Singh; Caslav Lacnjevac; Murugan Naga Jothi; Pooviah Shanthy (Zaštita Materijala, 2024)
The inhibition efficiency of  an aqueous extract of apple juice in controlling corrosion of mild steel  immersed in simulated concrete pore solution (SCPS) prepared in sea water, has been evaluated by weight loss method. Langmuir adsorption isotherm has been investigated. The mechanistic aspect of corrosion inhibition has been investigated by Electrochemical impedance spectra (AC impedance spectra). The protective film has been analysed by Fluorescence spectroscopy, FTIR spectroscopy and AFM. The SCPS system offers 60% inhibition efficiency to mild steel immersed in sea water. In presence of apple juice extract the inhibition efficiency increases as the concentration of the extract increases. When 10 ml of extract is added, 85% inhibition efficiency is obtained. Electrochemical impedance spectra (AC impedance spectra) reveal that a protective film is formed on the metal surface. In the presence of inhibitor system, charge transfer resistance value increases, impedance value increases, phase angle value increases whereas double layer capacitance value decreases as expected. The FTIR spectral study reveals that the protective film consists of complexes consisting of iron-active principles of the apple juice extract. AFM study reveals that when the inhibition efficiency increases the roughness of the surface decreases or in other words the smoothness of the system increases.